Tree species diversity promotes soil microbial carbon fixation gene abundance via nutrient-mediated interactions in subtropical forests - Su, Siwen; Pan, Jinwen; Wu, Huili; Ouyang, Shuai; Chen, Liang; Zeng, Yelin; Deng, Nan (Frontiers in Microbiology, 2026)
Soil microbial carbon (C) fixation represents a vital yet uncertain component of forest carbon cycling, and its underlying mechanisms especially depth-specific responses remain unclear. To address this, we integrated metagenomics and machine learning to examine these relationships along a tree species richness gradient (1–8 species), analyzing both topsoil (0–10 cm) and subsoil (10–20 cm). Results revealed distinct vertical stratification in soil properties and microbial carbon fixation strategies. Microbial carbon fixation gene abundance was primarily driven by soil organic carbon (SOC) and nitrate nitrogen (NO₃−-N), exhibiting a nonlinear threshold at ~85 g kg−1 SOC. The promoting effect of SOC peaked at moderate richness (3–5 species) but declined at higher richness. Depth-resolved analysis revealed that the Calvin cycle gene rbcL responded mainly to richness in topsoil, whereas rTCA cycle genes (korA, korC) were more sensitive in subsoil These findings demonstrate that tree diversity enhances microbial carbon fixation through nutrient-mediated mechanisms, but these effects are nonlinear, context-dependent, and depth-specific. Incorporating such complexity is essential for accurately predicting forest carbon sequestration.